2014
DOI: 10.1021/jz501973d
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Hydroxamate a Promising Anchoring Group in Dye-Sensitized Solar Cells? Insights from Theoretical Investigation

Abstract: We report, from a theoretical point of view, the first comparative study between the highly water-stable hydroxamate and the widely used carboxylate, in addition to the robust phosphate anchors. Theoretical calculations reveal that hydroxamate would be better for photoabsorption. A quantum dynamics description of the interfacial electron transfer (IET), including the underlying nuclear motion effect, is presented. We find that both hydroxamate and carboxylate would have efficient IET character; for phosphate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 53 publications
(117 reference statements)
0
26
0
Order By: Relevance
“…Experimental and theoretical studies on TiO2 have shown that organic carboxylate and hydroxamate anchoring groups exhibit faster interfacial electron transfer because of a better electronic coupling at the oxide interface compared to phosphonate anchoring groups. [16][17][18] This latter poor coupling may arise from the tetrahedral geometry of the phosphorous atom and the loss of conjugation through to the oxide. 78 At the expense of their electronic behaviour, phosphonate and silanederived anchoring groups exhibit greater stabilities, with phosphonate anchoring groups showing stabilities that are orders of magnitude greater than carboxylate anchoring groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and theoretical studies on TiO2 have shown that organic carboxylate and hydroxamate anchoring groups exhibit faster interfacial electron transfer because of a better electronic coupling at the oxide interface compared to phosphonate anchoring groups. [16][17][18] This latter poor coupling may arise from the tetrahedral geometry of the phosphorous atom and the loss of conjugation through to the oxide. 78 At the expense of their electronic behaviour, phosphonate and silanederived anchoring groups exhibit greater stabilities, with phosphonate anchoring groups showing stabilities that are orders of magnitude greater than carboxylate anchoring groups.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] While each has its own merits in terms of stability and charge transfer properties, one usually comes at the expense of the other. [16][17][18] For example, phosphonate and carboxylate anchoring groups readily desorb in the alkaline pH's favoured for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) when catalysed by non-precious metal compounds. Furthermore, the electrochemical stability of such non-covalent binding motifs is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical anchor groups consisting of a molecular subunit or just a single atom are used to determine these parameters for a class of molecules. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Recently, platform molecules have been used as anchors to a substrate and to achieve decoupling from neighbor molecules. 16,17 Extended aromatic platforms are particularly interesting because they adhere to a substrate via physisorption instead of chemisorption.…”
Section: Introductionmentioning
confidence: 99%
“…The bidentate binding mode was used as the binding mode for the dye adsorption onto the (TiO 2 ) 38 cluster. This binding mode is the most stable form for the adsorption of dyes with cyanoacrylic acid acceptors (Li et al, 2014b). The (TiO 2 ) 38 cluster model has been widely used to investigate the dye/TiO 2 interaction with smaller computation cost.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent effect was included with the polarizable continuum model (PCM) (Cossi et al, 2002). To reduce the computational cost, the long alkyl chains of all dyes were replaced by methyl groups, which has been validated in previous works (Li et al, 2014b). The charge recombination between the injected electron and electrolyte was evaluated by calculating the binding energy of I 2 to different binding sites of the dye.…”
Section: Computational Detailsmentioning
confidence: 99%